The Indonesia’s Racehorse Reproductive Performance - Elvira Nur Saqinah; Tetty Barunawati Siagian (UNIVERSITAS ISLAM LAMONGAN, 2022)
The need for equestrian sport is increasing for local horse grading with Thoroughbred horses used for racehorses. Pamulang Equestrian Centre is one of the horse farms in Indonesia that acts as a pioneer in creating local Indonesian racehorses. The purpose of this paper is to explain the reproductive performance of the Indonesian Kuda Pacu Indonesia (KPI) through a case study at Pamulang Equestrian Centre. Primary data was obtained directly from the documentation and interviews of the farmers. Meanwhile, secondary data was collected from literature studies. Horse farming at Pamulang Equestrian Centre was the result of breeding horses G3 with G3, G3 with G4, G4 with G4, G3 or G4 with KPI that produced KPI. Horse breeding was carried out annually during the breeding season, from August to January. The reproductive performance of male and female KPI at Pamulang Equestrian Centre was mating time from August to January, at the age of first estrus was 12-15 months, the first mating age was 4 years, estrus duration was 7 days, and duration of gestation was approximately 11 Months.